Analisis Perbandingan Kinerja Keuangan Dan Ekonomi Sosial Bank Syariah Antara Sebelum Dan Sesudah Ditetapkannya Fatwa MUI Tentang Haramnya Bunga Bank - Lia Auliah Rachmah; Nisful Laila (Universitas Airlangga, 2016)
This study aims to find out the comparison between the performance of Islamic Banks including financial performances such as the ratio of ROA, ROE, FDR and CAR as wells economic and social performance such as MMR ratio before and after the determination of fatwa regarding the prohibition against bank interest. Quantitative approach and independent sample t-test has been used in this study. The data is a secondary data which was obtained by collecting the annual financial reports. The result of the independent sample t-test shows that there are significant differences between the performance of the Islamic banks before and after the fatwa on the ratio of ROE, FDR and MMR. Whereas on the ratio of ROA and CAR have no significant difference before and after the fatwa.